Profiling Racial - um estudo preliminar - Corina Liliana Marques dos Santos (2021)
Over time, several studies have been developed, particularly in the American context, where police officers and judges resort to "racial profiling" when taking a court decision. Racial profiling refers to the stereotype associated with race that can, according to studies, negatively influence the behavior of these agents. Given the scarcity of literature in the national context, this study sought to investigate, through a convenience sample and using crime videos, the severity of the application of a hypothetical penal measure to a black and a caucasian aggressor and to what extent this penalty is conditioned by the race of the participant who watched the videos (caucasian and black). The results demonstrated that the Caucasian group showed an in-group preference (the group to which they belong) and the black group showed an out-group preference (i.e., for the Caucasians). As for the seriousness of the penalty, both aggressors were sanctioned with the same measure.